Clinical anatomy aspects of functional 3D training - case study - Pastucha, Dalibor; Filipcikova, Radka; Bezdickova, Marcela; Blazkova, Zdenka; Oborna, Ivana; Brezinova, Jana; Machalek, Libor; Sovova, Eliska; Cajka, Vit; Bajorek, Jan (Biomedical papers, 2012)
Introduction: Functional 3D training originating in rehabilitation and physiotherapy routines, is modelled on the basis of a patient's functional impairment and muscle function test results. 3-D functional rehabilitation comprises two key components. The first is three-dimensional movements of the body and the second is restoration of function, The aim of 3D training is not only to improve physical fitness and muscular coordination, it is recommended for all age groups regardless of health status. The aim of this review is to highlight the main principles, roles and methods of 3D functional training from a clinically-anatomical perspective and its application in clinical practice. Second, we present a case study of 3d training in an obese boy.Methods: Database search using the lemmatization method and data bases: Web of Knowledge, Web of Science, UpToDate, PubMed and Google Scholar for the years 2005-2011.Results and Conclusions: Functional 3D training is an effective method for, among others, strengthening the postural muscles of the human body, increasing articular stability, strengthening the ligaments and stability of muscle groups,especially the back muscles and for improving lung capacity. The method of functional training is of considerable significance in activating the pelvic floor muscles and the pelvic-trochanteric muscles for gynegymnastics and incontinence prevention. It has application in the prevention of falls in patients with neurodegenerative diseases and, as shown below, in the therapy of obesity.
Keywords: 3D training; resistance training; obesity; children